Creating the conditions for self-fulfilment for aged care residents - Brownie, Sonya (Nursing ethics, 2012)
In 1991 the United Nations General Assembly adopted the Principles for Older Persons as a framework for international policy responses to population ageing. These principles promote independence, participation, care, self-fulfilment and dignity as legitimate entitlements of all older people. Although these principles, or variations of them, are embedded in standards of best-practice in residential aged care facilities, the literature shows that in reality institutional care can deny older people opportunities to exercise some of these entitlements. More specifically, residential aged care facilities can deprive older people of access and support to pursue opportunities for the full development of their potential, i.e. their entitlement to self-fulfilment. This discussion article explores the influence of institutional care on older people’s ability to exercise their entitlement to self-fulfilment. We identify the characteristics of a ‘good life’ in institutional care, according to aged care residents themselves. The Eden Alternative™ is presented as a model of aged care that aims to create the conditions for a ‘good life’ and self-fulfilment for aged care residents.